2014
DOI: 10.1177/2325967114s00046
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Predictors Of Subsequent ACL Injury After ACL Reconstruction: Prospective Analysis Of 2801 Primary ACL Reconstructions

Abstract: Objectives:Retear of an ACL after an ACL reconstruction (ACLR) is devastating for all involved. Understanding risk factors and predictors of subsequent ACL tear after an ACLR is vital for patient education of subsequent risk of injury and if a predictor is modifiable, to make adjustments to minimize the risk of repeat ACL tear. The objectives of this study were 1) to identify the risk factors and predictors for ispilateral and contralateral ACL tears after primary ACLR and 2) to compare retear risk between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

20
386
6
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 242 publications
(426 citation statements)
references
References 0 publications
20
386
6
2
Order By: Relevance
“…Although ACL reconstruction is a successful operation, resulting in a high likelihood of return to play, recent data from the Multicenter Orthopaedic Outcomes Network group and others found that its results are not as good as we think, particularly in young patients and high-level (high school and collegiate) athletes [1,2]. Many patients do not return to activities that they previously participated in, and some studies [1,2] have found a high frequency of ACL graft rupture and contralateral ACL rupture, particularly in young, active patients in the first 1 to 2 years after reconstruction.…”
mentioning
confidence: 62%
“…Although ACL reconstruction is a successful operation, resulting in a high likelihood of return to play, recent data from the Multicenter Orthopaedic Outcomes Network group and others found that its results are not as good as we think, particularly in young patients and high-level (high school and collegiate) athletes [1,2]. Many patients do not return to activities that they previously participated in, and some studies [1,2] have found a high frequency of ACL graft rupture and contralateral ACL rupture, particularly in young, active patients in the first 1 to 2 years after reconstruction.…”
mentioning
confidence: 62%
“…With regard to ligament reconstructions in young athletes in general, it has been well documented that the use of allograft tissue for primary ACL reconstruction in young athletes is associated with an increased risk of graft rupture [3,4,7]. However, given the dissimilarities between the ACL and the MPFL in terms of anatomy and function, it may not be appropriate to apply findings from the ACL literature to those patients undergoing MPFL reconstruction.…”
mentioning
confidence: 99%
“…157 About 45% of reconstructions use the BPTB autograft compared to approximately 36% with HG, with the remaining 19% of reconstructions using an allograft. 83,92 Both autograft reconstructions (BPTB and HG) are currently more common than allograft reconstructions. 83,92 Autograft choice does not alter clinical outcomes after ACLR, 81 with exception to increased anterior knee and kneeling pain with BPTB.…”
Section: Incidence Of Anterior Cruciate Ligament Injuriesmentioning
confidence: 99%
“…83,92 Both autograft reconstructions (BPTB and HG) are currently more common than allograft reconstructions. 83,92 Autograft choice does not alter clinical outcomes after ACLR, 81 with exception to increased anterior knee and kneeling pain with BPTB. 127 …”
Section: Incidence Of Anterior Cruciate Ligament Injuriesmentioning
confidence: 99%
See 1 more Smart Citation